Low-water-absorption voltage-resistant polyurethane acrylate adhesive and preparation method thereof

By introducing specific hydrophobic agents and polyfunctional glycidyl ether epoxy resins into polyurethane acrylate glue, the problem of high water absorption in high humidity environments is solved, and its voltage resistance, adhesion and anti-aging properties are significantly improved, and the service life of components is extended.

CN119875567AActive Publication Date: 2025-04-25广东省博翔新材料有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510095674.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Polyurethane acrylate glue has high water absorption rate in high humidity environments, resulting in reduced voltage resistance, adhesion and aging resistance, affecting the stability and service life of components.

Method used

A water repellent composed of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiloxol were used to prepare low-water absorption and voltage-resistant polyurethane acrylate glue.

Benefits of technology

It significantly reduces the water absorption rate of polyurethane acrylate glue, improves its voltage resistance, adhesion and anti-aging properties in high humidity environments, and extends the service life and reliability of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005252819090000061
    Figure BDA0005252819090000061
  • Figure BDA0005252819090000071
    Figure BDA0005252819090000071
  • Figure BDA0005252819090000091
    Figure BDA0005252819090000091
Patent Text Reader

Abstract

The invention relates to the field of polyurethane acrylate adhesives, in particular to a low-water-absorption voltage-resistant polyurethane acrylate adhesive and a preparation method thereof.The low-water-absorption voltage-resistant polyurethane acrylate adhesive is prepared from, by weight, 45-55% of polyurethane acrylate, 8-12% of polyfunctional group glycidyl ether epoxy resin, 1-2% of an initiator, 4-6% of a water repellent and the balance reactive diluent; the water repellent is prepared from fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsilanolate. The low-water-absorption voltage-resistant polyurethane acrylate adhesive prepared according to the formula has good voltage resistance and low water absorption; the problems that components such as a connector, a nickel sheet and a negative temperature coefficient thermistor are unstable in bonding, easy to age, reduced in mechanical property and the like in a high-humidity environment can be effectively solved. By applying the adhesive, the reliability and durability of the components in a humid environment can be remarkably improved, and the service life of the components is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polyurethane acrylate adhesives, and more specifically, to a low water absorption and voltage-resistant polyurethane acrylate adhesive and a preparation method thereof. Background Art

[0002] Polyurethane acrylate adhesive is mainly used in components such as connectors, nickel sheets, and negative temperature coefficient thermistors to ensure that the various components of the connector, the nickel sheets, and the negative temperature coefficient thermistors can be firmly bonded. However, components such as connectors, nickel sheets, and negative temperature coefficient thermistors are sometimes used in high-humidity environments, such as connectors used in meteorological stations, environmental monitoring equipment, etc. These devices are usually exposed to the natural environment and are easily affected by moisture factors such as rain and fog; such as batteries, fuel cells, etc. These devices will produce chemical reactions during operation, causing the humidity of the surrounding environment to increase, making the nickel sheet in a high-humidity environment; negative temperature coefficient thermistors are used in outdoor temperature measurement equipment, such as agricultural meteorological monitoring stations, environmental monitoring equipment, etc. These devices are usually exposed to the natural environment and are easily affected by moisture factors.

[0003] High humidity can cause the size of urethane acrylate adhesive to increase, which may affect its physical and chemical properties. Specifically, it will reduce the voltage resistance of urethane acrylate adhesive, which means that under humid conditions, the insulation properties of the adhesive may be impaired, increasing the risk of circuit shorts or electrical failures. In addition, the bonding performance will also be reduced, causing the connection between components to become unstable, and may even fall off or break. At the same time, the anti-aging and mechanical properties will also be affected by the humid environment. When in a high humidity environment for a long time, urethane acrylate adhesive may accelerate aging, crack, harden or soften, etc., thereby reducing its service life and reliability. Mechanical properties, such as tensile strength and shear strength, may also be reduced, affecting the overall stability and durability of components. Summary of the invention

[0004] In order to reduce the water absorption of polyurethane acrylate adhesive and enhance its voltage resistance, adhesion and aging resistance, the present application provides a low water absorption voltage-resistant polyurethane acrylate adhesive and a preparation method thereof.

[0005] In the first aspect, the present application provides a low water absorption voltage-resistant polyurethane acrylate adhesive, which adopts the following technical solution: A low water absorption voltage-resistant polyurethane acrylate adhesive is prepared from the following raw materials in percentage by weight: Polyurethane acrylate 45-55% Multifunctional glycidyl ether epoxy resin 8-12% Photoinitiator 1-2% Water repellent 4-6% The remaining amount is active diluent; The water repellent is composed of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate.

[0006] By adopting the above technical solution, polyurethane acrylate is used as the main matrix resin to ensure good bonding performance and physical and mechanical properties. At the same time, multifunctional glycidyl ether epoxy resin is added to enhance the crosslinking density and chemical resistance of the colloid, thereby improving its voltage resistance performance. The hydrophobic agent composed of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate in this application can significantly reduce the water absorption rate of the colloid and effectively prevent moisture from penetrating into the interior of the colloid, thereby avoiding problems such as size increase and reduced voltage resistance.

[0007] The ethoxy segments in the molecular structure of fatty alcohol polyoxyethylene (3) ether can form an effective hydrophobic barrier to prevent the penetration of water molecules. Polydimethylsiloxane and fatty alcohol polyoxyethylene (3) ether work synergistically to form a denser hydrophobic layer, effectively reducing the water absorption rate of the colloid. Sodium methylsiliconate is an auxiliary component, which helps to adjust the overall performance of the hydrophobic agent and make it more stable. That is, the addition of the hydrophobic agent effectively prevents water from penetrating into the colloid, reduces the risk of size increase and reduced voltage resistance due to water absorption, and thus improves the safety and stability of the circuit. Even in a humid environment, the colloid can still maintain good bonding strength, ensure a firm connection between components, and avoid falling off or breaking. The hydrophobic agent can also effectively prevent the colloid from accelerating aging due to water absorption, maintain its good tensile strength, shear strength and other mechanical properties, and extend the service life and reliability of components.

[0008] Preferably, the weight ratio of the fatty alcohol polyoxyethylene (3) ether, the polydimethylsiloxane and the sodium methyl siliconate is 10:(3-5):1.

[0009] By adopting the above technical solution, the dosage of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate is optimized, the hydrophobicity of polyurethane acrylate adhesive is further enhanced, the penetration of water molecules is effectively blocked, and its voltage resistance performance in high humidity environment is significantly improved, ensuring the safety and stability of electrical insulation. At the same time, this combination can also maintain the stable adhesion of the colloid under humid conditions, avoiding the detachment or breakage of the connecting parts, thereby enhancing the overall durability and reliability of the components. In addition, this ratio also helps to improve the anti-aging and mechanical properties of the colloid, extending the service life of the components.

[0010] Preferably, the polyurethane acrylate is obtained by the following method: 1) adding isooctyl acrylate, methyl methacrylate, acrylamide, silicone monomer and initiator into a reactor, heating to 75-85° C., and reflux heating for 2-3 hours to obtain an acrylate polymer; 2) Add polypropylene glycol and polyether polyol into a reactor, then place in an oil bath at 110-120°C, heat and stir, and vacuum treat; when the reactor reaches 110-120°C, add isocyanate and catalyst under the protection of nitrogen, react for 1-1.5h to end the reaction; then vacuum distill under reduced pressure to remove bubbles in the product for 0.5h; when there are no bubbles in the product, introduce nitrogen, adjust the reaction temperature to 90-95°C, add hydroxyethyl acrylate, react for 1-1.5h to obtain a polyurethane polymer; 3) Adding the acrylate polymer and the polyurethane polymer into the reactor, heating to 80-85° C. and reacting for 2-3 hours to obtain polyurethane acrylate.

[0011] By adopting the above technical solution, the acrylate polymer and the polyurethane polymer are effectively combined to form a polyurethane acrylate that has the advantages of both. The acrylate polymer gives the product good weather resistance, water resistance and glossiness, while the polyurethane polymer brings excellent flexibility, wear resistance and adhesion.

[0012] By precisely controlling the polymerization reaction of isooctyl acrylate, methyl methacrylate, acrylamide, silicone monomer and initiator, an acrylate polymer with stable structure and excellent performance is obtained. This step not only ensures the regular arrangement of polymer segments, but also makes the polymer have good water resistance and weather resistance, and can effectively reduce the water absorption of polyurethane acrylate. Through the reaction of polypropylene glycol, polyether polyol and isocyanate, a polyurethane polymer is formed, which further enhances the overall hydrophobicity. This enhanced hydrophobicity helps to reduce the absorption of water molecules and improve the water resistance of the product. The acrylate polymer and the polyurethane polymer are connected together by chemical bonds, which further improves the compactness and hydrophobicity of the overall structure. This compact structure helps to reduce the penetration channels of water molecules, thereby further reducing the water absorption rate.

[0013] At the same time, since both acrylate polymers and polyurethane polymers have good insulation properties, the polyurethane acrylate obtained by copolymerization also has excellent insulation properties. This improvement in insulation properties helps reduce the risk of electrical breakdown of products under high voltage, thereby improving their voltage resistance.

[0014] Preferably, the weight ratio of the isooctyl acrylate, the methyl methacrylate, the acrylamide, the silicone monomer and the initiator is 10:(0.5-1):(2-3):(1-2):(0.2-0.5).

[0015] By adopting the above technical scheme and optimizing the usage ratio of various raw materials, the structure and properties of acrylate polymers can be precisely controlled. The final polyurethane acrylate adhesive has lower water absorption, higher voltage resistance and more stable bonding performance. It can maintain excellent physical and chemical properties in a high humidity environment and meet the bonding requirements of various components.

[0016] Preferably, the weight ratio of the polypropylene glycol, the polyether polyol, the isocyanate, the catalyst and the hydroxyethyl acrylate is 10:(4-8):(6-9):(0.1-0.3):(0.3-0.5).

[0017] By adopting the above technical solution, the synthesis process of the polyurethane polymer can be accurately controlled, which not only ensures that the polyurethane polymer has excellent chemical resistance and physical properties, but also provides a stable skeleton and functional groups for the subsequent synthesis of polyurethane acrylate.

[0018] Preferably, the weight ratio of the acrylate polymer to the polyurethane polymer is 1:(2-3).

[0019] By adopting the above technical solution, the complementary advantages of the two in structure and performance can be fully utilized. Acrylate polymer provides good flexibility and weather resistance, while polyurethane polymer enhances chemical resistance and physical strength. With this ratio, the polyurethane acrylate adhesive prepared not only has lower water absorption and higher voltage resistance, but also has more stable bonding performance and can maintain excellent performance in high humidity environments. This optimized ratio makes polyurethane acrylate adhesive more suitable for component bonding under various harsh conditions, improving the reliability and durability of the overall product.

[0020] Preferably, the organosilicon monomer is vinyltriethoxysilane and / or methacryloxypropyltrimethoxysilane.

[0021] By precisely controlling the ratio and reaction conditions of these two silicone monomers, polyurethane acrylate adhesive with lower water absorption, higher voltage resistance and more stable bonding performance can be produced to meet the bonding needs of various high-demand components.

[0022] Preferably, the active diluent is at least one of neopentyl glycol glycidyl ether, diethylene glycol glycidyl ether, benzyl glycidyl ether, tert-butylphenol glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, n-octanol glycidyl ether, C12-14 alcohol glycidyl ether, phenyl glycidyl ether, o-cresol glycidyl ether, ethylene glycol glycidyl ether, butanediol glycidyl ether, hexanediol glycidyl ether, glycerol glycidyl ether, and trimethylolpropane glycidyl ether.

[0023] By adopting the above technical solution, not only can the viscosity of the colloid be effectively adjusted, which is convenient for processing and application, but also good compatibility can be formed with the main resins such as polyurethane acrylate and multifunctional glycidyl ether epoxy resin. At the same time, they can also participate in the polymerization reaction to improve the crosslinking density and stability of the colloid. Therefore, the polyurethane acrylate adhesive prepared by using these active diluents has lower water absorption, higher voltage resistance and more stable bonding performance, and can maintain excellent physical and chemical properties in a high humidity environment, meeting the bonding requirements of various components.

[0024] In a second aspect, the present application provides a method for preparing a low water absorption voltage-resistant polyurethane acrylate adhesive, which adopts the following technical solution: A method for preparing a low water absorption voltage-resistant polyurethane acrylate adhesive comprises the following steps: The polyurethane acrylate, multifunctional glycidyl ether epoxy resin, photoinitiator, hydrophobic agent and active diluent are uniformly stirred to obtain low water absorption and voltage-resistant polyurethane acrylate adhesive.

[0025] By adopting the above technical scheme, polyurethane acrylate, multifunctional glycidyl ether epoxy resin, photoinitiator, hydrophobic agent and active diluent can be fully mixed to form a uniform and stable polyurethane acrylate adhesive with low water absorption and voltage resistance.

[0026] In summary, this application has the following beneficial effects: 1. Low water absorption: By introducing hydrophobic agents, the penetration of water molecules can be effectively blocked, the water absorption rate can be reduced, and the dimensional stability of the colloid can be maintained in a high humidity environment.

[0027] 2. Improved voltage resistance: The addition of hydrophobic agent not only reduces water absorption, but also enhances the insulation performance of polyurethane acrylate adhesive, reducing the risk of circuit short circuit or electrical failure under humid conditions.

[0028] 3. Stable bonding performance: By using polyurethane acrylate, polyurethane acrylate glue multifunctional glycidyl ether epoxy resin, photoinitiator, hydrophobic agent and active diluent together, polyurethane acrylate glue can still maintain stable bonding performance in a high humidity environment, ensuring that the connection between components is firm and reliable, and not prone to falling off or breaking. At the same time, it also improves the tolerance of polyurethane acrylate glue to humid environments, reduces the occurrence of aging, and prolongs its service life. DETAILED DESCRIPTION Example

[0029] The polyurethane acrylate in Examples 1-3 was purchased from Hunan Jinhai Technology Co., Ltd. with a brand name of JS312.

[0030] The multifunctional glycidyl ether epoxy resin in Examples 1-3 was purchased from Guangzhou Huali Trading Co., Ltd., and the model number was American Hanson multifunctional epoxy resin EPON 1031.

[0031] The polydimethylsiloxane in Example 1-3 was purchased from Shenzhen Xinyongsheng New Materials Co., Ltd. with model number 26710-23-6.

[0032] Polypropylene glycol was purchased from Haian Petrochemical Plant in Jiangsu Province, model PPG-425.

[0033] Polyether diol D2000 was purchased from Haian Petrochemical Plant in Jiangsu Province with the brand name DL-2000D.

[0034] Example 1 A low water absorption voltage-resistant polyurethane acrylate adhesive is prepared by the following method: 450 g of polyurethane acrylate, 120 g of multifunctional glycidyl ether epoxy resin, 20 g of photoinitiator (1-hydroxycyclohexyl phenyl ketone), 60 g of hydrophobic agent and 350 g of active diluent (neopentyl glycol glycidyl ether) were stirred uniformly to obtain low water absorption and voltage-resistant polyurethane acrylate adhesive.

[0035] The water repellent is composed of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate in a weight ratio of 10:3:1.

[0036] Example 2 A low water absorption voltage-resistant polyurethane acrylate adhesive is prepared by the following method: 500 g of polyurethane acrylate, 100 g of multifunctional glycidyl ether epoxy resin, 15 g of photoinitiator (phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide), 50 g of hydrophobic agent and 335 g of active diluent (diethylene glycol glycidyl ether) were stirred evenly to obtain low water absorption and voltage-resistant polyurethane acrylate adhesive.

[0037] The water repellent is composed of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate in a weight ratio of 10:4:1. Example 3 A low water absorption voltage-resistant polyurethane acrylate adhesive is prepared by the following method: 500 g of polyurethane acrylate, 80 g of multifunctional glycidyl ether epoxy resin, 10 g of photoinitiator (phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide), 40 g of hydrophobic agent and 370 g of active diluent (tert-butylphenol glycidyl ether) are stirred evenly to obtain low water absorption and voltage-resistant polyurethane acrylate adhesive.

[0038] The water repellent is composed of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate in a weight ratio of 10:5:1.

[0039] Example 4 A low water absorption and voltage-resistant polyurethane acrylate adhesive. The difference between this embodiment 1 is that the weight ratio of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate is 10:10:1.

[0040] Example 5 A low water absorption and voltage-resistant polyurethane acrylate adhesive. The difference of this embodiment 1 is that the polyurethane acrylate is obtained by the following method: 1) Add 200 g of isooctyl acrylate, 10 g of methyl methacrylate, 40 g of acrylamide, 20 g of silicone monomer (vinyl triethoxysilane) and 4 g of initiator (dibenzoyl peroxide) into a reactor, heat to 75° C., and reflux for 2 h to obtain an acrylate polymer; 2) Add 400 g of polypropylene glycol and 160 g of polyether polyol into a reactor, then place in an oil bath at 110° C., heat and stir, and vacuum treat; when the reactor reaches 110° C., add 220 g of isocyanate (isophorone diisocyanate) and 4 g of catalyst (dibutyltin dilaurate) under the protection of nitrogen, and react for 1 hour to terminate the reaction; then vacuum distill under reduced pressure to remove bubbles in the product for 0.5 hour; when there are no bubbles in the product, introduce nitrogen, adjust the reaction temperature to 90° C., add 12 g of hydroxyethyl acrylate, and react for 1 hour to obtain a polyurethane polymer; 3) 200 g of acrylate polymer and 400 g of polyurethane polymer were added into a reactor, and the temperature was raised to 80° C. to react for 2 h to obtain polyurethane acrylate.

[0041] The difference between Example 6-7 and Example 5 is that the types of raw materials, amounts and experimental parameters for preparing polyurethane acrylate are different. The specific differences are shown in Table 1: Table 1 Raw material types, amounts and experimental parameters for preparing polyurethane acrylate Example 8 A low water absorption and voltage-resistant polyurethane acrylate adhesive. The difference of this embodiment 5 is that the weight ratio of the acrylate polymer to the polyurethane polymer is 1:1.

[0042] Example 9 A low water absorption and voltage-resistant polyurethane acrylate adhesive. The difference of this embodiment 5 is that styrene is used instead of vinyl triethoxy silane.

[0043] Comparative Example Comparative Example 1 A polyurethane acrylate adhesive. The difference between this comparative example and Example 1 is that fatty acid is used instead of the water repellent.

[0044] Comparative Example 2 A polyurethane acrylate adhesive. The difference between this comparative example and Example 1 is that fatty acid polyoxyethylene ester is used instead of fatty alcohol polyoxyethylene (3) ether.

[0045] Comparative Example 3 A polyurethane acrylate adhesive. The difference between this comparative example and Example 1 is that ethyl stearate is used instead of polydimethylsiloxane.

[0046] Comparative Example 4 A polyurethane acrylate adhesive. The difference between this comparative example and Example 1 is that ethyl acetate is used instead of sodium methyl siliconate.

[0047] Comparative Example 5 A polyurethane acrylate adhesive. The difference between this comparative example and Example 1 is that methyl glycidyl ether epoxy resin is used instead of multifunctional glycidyl ether epoxy resin.

[0048] Methyl glycidyl ether epoxy resin was purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd. with a CAS number of 61788-97-4.

[0049] Detection method / test method Water absorption rate: refer to the test method of water absorption rate of plastics in standard ASTM D570-05 for testing. The low water absorption and voltage-resistant polyurethane acrylate adhesive of Examples 1-9 and the polyurethane acrylate adhesive of Comparative Examples 1-5 are cured to prepare specimens of 76.2 mm×25.4 mm×3.2 mm. The water absorption after immersion in water at 23°C for 24 hours is tested, and the water absorption rate is calculated according to the formula in the standard.

[0050] Shear strength: The low water absorption and voltage-resistant polyurethane acrylate adhesive of Example 1-9 and the polyurethane acrylate adhesive of Comparative Example 1-5 were coated between two substrates, where the two substrates were a stainless steel test piece and a PET substrate, and the tensile shear strength was tested according to GB / T7124-2008.

[0051] Voltage resistance: refer to GB / T 16927.1-2011.

[0052] Reliability test: 1) The low water absorption and withstand voltage polyurethane acrylate adhesive of Example 1-9 and the polyurethane acrylate adhesive of Comparative Example 1-5 were subjected to a double 85 aging test under the following conditions: placed in a constant temperature and humidity chamber at 85°C and 85RH% for 1008h, then taken out and dried, and the shear strength was retested.

[0053] 1. The low water absorption and withstand voltage polyurethane acrylate adhesive of Examples 1-9 and the polyurethane acrylate adhesive of Comparative Examples 1-5 were subjected to high and low temperature aging tests, with the conditions of -40°C / 12h, 120°C / 12h, a total of 500h of high temperature and low temperature cycles, and the adhesive shear strength was retested. The experimental data are shown in Table 2: Table 2 Experimental data of embodiments and comparative examples By comparing Example 1 with Comparative Examples 1-4, the water absorption rates of Comparative Examples 1-4 are all greater than that of Example 1, and the shear strengths are all less than that of Example 1; the voltage resistance of Comparative Examples 1 and 3 is lower than that of Example 1; after the double 85 aging test and the high and low temperature aging test, the shear strength change of Comparative Examples 1-4 is greater than that of Example 1, indicating that the present application can effectively reduce the water absorption of polyurethane acrylate adhesive and improve its voltage resistance, shear strength and anti-aging performance by adding fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate as hydrophobic agents.

[0054] By comparing Example 1 with Comparative Example 5, the water absorption rate of Comparative Example 5 is greater than that of Example 1, and the shear strength is less than that of Example 1; after the double 85 aging test and the high and low temperature aging test, the shear strength change of Comparative Example 5 is greater than that of Example 1, indicating that the addition of multifunctional glycidyl ether epoxy resin can effectively reduce the water absorption of polyurethane acrylate adhesive, and improve its shear strength and anti-aging performance.

[0055] Comparing Example 1 with Example 4, the water absorption rate of Example 4 is greater than that of Example 1, and the shear strength is less than that of Example 1; after the double 85 aging test and the high and low temperature aging test, the shear strength change of Example 4 is greater than that of Example 1, indicating that optimizing the dosage of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate can effectively reduce the water absorption of polyurethane acrylate adhesive and improve its voltage resistance, shear strength and anti-aging performance.

[0056] Comparing Example 1 with Example 5-7, the water absorption of Example 5-7 is less than that of Example 1, and the shear strength is greater than that of Example 1; the voltage resistance of Example 5-7 is higher than that of Example 1; after the double 85 aging test and the high and low temperature aging test, the shear strength change of Example 5-7 is less than that of Example 1; By comparing Example 5 with Example 8, the water absorption rate of Example 5 is lower than that of Example 8, and the shear strength is higher than that of Example 1; the voltage resistance of Example 5 is higher than that of Example 8; after the double 85 aging test and the high and low temperature aging test, the shear strength change of Example 5 is lower than that of Example 8; By comparing Example 5 with Example 9, the water absorption rate of Example 5 is lower than that of Example 9, and the shear strength is higher than that of Example 1; the voltage resistance of Example 5 is higher than that of Example 9; after the double 85 aging test and the high and low temperature aging test, the shear strength change of Example 5 is lower than that of Example 9; From the data of Examples 1, 5-7, 8, and 9, it can be seen that the polyurethane polypropylene prepared by the present application can effectively reduce the water absorption of polyurethane acrylate adhesive and improve its voltage resistance, shear strength, and anti-aging performance.

[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low water absorption voltage-resistant polyurethane acrylate adhesive, characterized in that: Prepared from the following raw materials in weight percentage: Polyurethane acrylate 45-55% Multifunctional glycidyl ether epoxy resin 8-12% Photoinitiator 1-2% Water repellent 4-6% The remaining amount is active diluent; The water repellent is composed of fatty alcohol polyoxyethylene (3) ether, polydimethylsiloxane and sodium methylsiliconate.

2. The low water absorption voltage-resistant polyurethane acrylate adhesive according to claim 1, characterized in that: The weight ratio of the fatty alcohol polyoxyethylene (3) ether, the polydimethylsiloxane and the sodium methyl siliconate is 10:(3-5):

1.

3. The low water absorption voltage-resistant polyurethane acrylate adhesive according to claim 1, characterized in that: The polyurethane acrylate is obtained by the following method: 1) Add isooctyl acrylate, methyl methacrylate, acrylamide, silicone monomer and initiator into a reactor, raise the temperature to 75-85°C, and reflux for 2-3 hours to obtain an acrylate polymer; 2) Add polypropylene glycol and polyether polyol into the reactor, then place in an oil bath pot at 110-120°C, heat and stir, and vacuum treat; when the reactor reaches 110-120°C, add isocyanate and catalyst under the protection of nitrogen, and react for 1-1.5 hours to end the reaction; then vacuum distill under reduced pressure to remove bubbles in the product for 0.5 hours; when there are no bubbles in the product, introduce nitrogen, adjust the reaction temperature to 90-95°C, add hydroxyethyl acrylate, and react for 1-1.5 hours to obtain a polyurethane polymer; 3) Add the acrylate polymer and the polyurethane polymer into the reactor, raise the temperature to 80-85° C. and react for 2-3 hours to obtain polyurethane acrylate.

4. The low water absorption voltage-resistant polyurethane acrylate adhesive according to claim 3, characterized in that: The weight ratio of the isooctyl acrylate, the methyl methacrylate, the acrylamide, the silicone monomer and the initiator is 10:(0.5-1):(2-3):(1-2):(0.2-0.5).

5. The low water absorption voltage-resistant polyurethane acrylate adhesive according to claim 3, characterized in that: The weight ratio of the polypropylene glycol, the polyether polyol, the isocyanate, the catalyst and the hydroxyethyl acrylate is 10:(4-8):(6-9):(0.1-0.3):(0.3-0.5).

6. The low water absorption voltage-resistant polyurethane acrylate adhesive according to claim 3, characterized in that: The weight ratio of the acrylic ester polymer to the polyurethane polymer is 1:(2-3).

7. The low water absorption voltage-resistant polyurethane acrylate adhesive according to claim 3, characterized in that: The organic silicon monomer is vinyl triethoxysilane and / or methacryloxypropyl trimethoxysilane.

8. The low water absorption voltage-resistant polyurethane acrylate adhesive according to claim 1, characterized in that: The active diluent is at least one of neopentyl glycol glycidyl ether, diethylene glycol glycidyl ether, benzyl glycidyl ether, tert-butylphenol glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, n-octanol glycidyl ether, C12-14 alcohol glycidyl ether, phenyl glycidyl ether, o-cresol glycidyl ether, ethylene glycol glycidyl ether, butanediol glycidyl ether, hexanediol glycidyl ether, glycerol glycidyl ether, and trimethylolpropane glycidyl ether.

9. A method for preparing the low water absorption voltage-resistant polyurethane acrylate adhesive according to any one of claims 1 to 8, characterized in that: The following steps are involved: The polyurethane acrylate, multifunctional glycidyl ether epoxy resin, photoinitiator, hydrophobic agent and active diluent are uniformly stirred to obtain low water absorption and voltage-resistant polyurethane acrylate adhesive.

Citation Information

Patent Citations

  • Sealant with low shrinkage rate for encapsulating LED (light-emitting diode)

    CN104031592A

  • Method of preparing polyurethane hot melt adhesive with high temperature resistance

    US10781345B1

  • Flexibilized polyepoxide resins

    US5334654A